GNSS data of glacier motion in vertical and horizontal direction (summer 2017 and 2019) - Angelika Humbert; Veit Helm; Ole Zeising; Daniel Steinhage; Shfaqat Abbas Khan (PANGAEA, 2025)
The dataset contains GNSS observations of glacier motion, airborne radio echo sounding of englacial channels, airborne laser scanner data of supraglacial lake ground topography and supraglacial lake outlines from satellite remote sensing data of 79°N Glacier. The GNSS observations are from summer 2017 and 2019. The radar sounding of englacial channels was conducted in 2016, 2018 and 2021. The airborne laser scanner data was obtained in summer 2021. The supraglacial lake outlines are from 2005, 2012, 2015, 2019, 2020, 2022 and 2023. The data covers a supraglacial lake at 24.58969°W,79.14370°N. The purpose of data acquisition was to study supraglacial lake drainage mechanisms.
In: Humbert, A et al. (2025): Observations of glacier motion, radio echo sounding of englacial channels, laser scanner data of supraglacial lake ground topography and supraglacial lake outlines of 79°N Glacier, Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974774